Cancer Survivorship at the Intersections of Care and Personhood. Issue 1 (2nd January 2020) - Ramirez, Michelle; Janke, E. Amy; Grant, Marcia; Altschuler, Andrea; Hornbrook, Mark; Krouse, Robert S.
ABSTRACT: Surviving colorectal cancer following ostomy surgery with an intestinal stoma presents numerous challenges to the cultural category of full adult personhood. The foremost is managing unpredictable bowel activity. The technical management of the ostomy facilitated by biomedical specialists, is essential for personhood realignment. This article focuses on how some female long-term cancer survivors manage and adapt to this new fecal habitus by mobilizing various assemblages of care – receiving care, continuing to provide particular gendered forms of care, and returning to caregiving roles. These interdependent practices of care realign personhood, or at the very least, minimize the assaults that having an ostomy presents to the cultural category of full adult personhood.